2016
DOI: 10.1108/bfj-11-2014-0376
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of purchase intentions toward organic food on health consciousness and food safety with/under structural equation modeling

Abstract: Purpose – The purpose of this paper is to investigate the influences of natural content, food safety concern, health consciousness, and subjective knowledge on attitudes towards organic food and purchase intentions. Design/methodology/approach – Samples are collected in Taiwan from April to May 2014 with a total of 252 returned effective questionnaires. The data are analyzed by structural equation modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
153
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(211 citation statements)
references
References 56 publications
16
153
1
2
Order By: Relevance
“…Previous studies lack strong evidence that organic foods are significantly more nutritious than conventional foods, and a number of studies have revealed that consumers’ choice of organic food depends on the perceived benefits of organic food [25,35,36]. Researchers have found that health is one of the most prominent motives for organic food consumption [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies lack strong evidence that organic foods are significantly more nutritious than conventional foods, and a number of studies have revealed that consumers’ choice of organic food depends on the perceived benefits of organic food [25,35,36]. Researchers have found that health is one of the most prominent motives for organic food consumption [25].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified the determinants of organic food purchase such as knowledge, attitudes and price consciousness towards organic products [12,13]. In addition, many studies showed the conversion to organic farming can have a potential to improve the water quality dominated by agricultural land use [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Economic growth, urbanisation, globalisation and trade liberalisation has significantly impact consumers' food choices and preferences. The increasing consumers' demand towards organic food products are mainly due to food safety concern (Hsu, Chang & Lin, 2016;Wee, Ariff, Zakuan & Tajuddin, 2014), health benefits (Mohamad, Rusdi & Hashim, 2014) and environmental concern (Sia, Ooi, Chong, Lim & Low, 2013).…”
Section: Introductionmentioning
confidence: 99%